Borohydride reduction of azomethine bonds in beta-alanine Schiff base complexes - (:unkn) unknown (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2008)
Borohydride reduction of the azomethine bond in the Schiff base complexes of beta-alanine has been Studied. Ni(II), Pd(II) and Pt(II) complexes of N-beta-carboxyethyl-2-hydroxynaphthyl-ideneimine ((LH2)-H-1) N-beta-carboxyethyl-2-hydroxybenzylideneimine ((LH2)-H-2), and N-beta-carboxyethyl-N-2-hydroxynaphtylmethyleneamine ((LH2)-H-3) have been prepared. (LH2)-H-1 forms complexes with palladium as Pd((LH)-H-1)(2), in which carboxylic groups do not participate in the coordination. (LH2)-H-2 and (LH2)-H-3 behave as tridentate double charged ligands, giving complexes of the type ML2 center dot nH(2)O and ML3 center dot nH(2)O. Ni(II) gives binuclear complex [NiL(3 center dot)2H(2)O](2), No visible reaction of -C=N- bond reduction with borohydride has been observed for the (LH2)-H-1 complexes of Co(III) d(6), Ni(II) d(8), Pd(II) d(8), Zn(II) d(10) ions at 25 degrees C in dimethyl formamide. This tendency has also been observed for Ni(II) complex of salicylaldehyde based beta-alanine Schiff base, (LH2)-H-2, as well as Ni(II), Pd(II), Zn(II) complexes of salen. However, the C=N bond can be reduced with borohydride when it coordinates the metal ions, Cu(II), Co(II) and Mn(II). Ni(II) complexes of both Schiff bases are inactive against reduction. The reduction rates of Schiff bases and related activation energies have also been determined.
Keywords: ALPHA-AMINO-ACIDS; ENANTIOSELECTIVE BOROHYDRIDE; COBALT(II) COMPLEXES; KETONES; ISOMERISM; IMINES